Peran Bimbingan Dan Konseling Belajar Dalam Meningkatkan Motivasi Belajar Matematika Pada Peserta Didik Kelas VII-8 SMPN 3 Palangkaraya Tahun Pelajaran 2014/2015 - Esty Aryani Safithry (Anterior Jurnal, 2015)
This study aimed to describe the role of guidance and counseling in motivating students to learn mathematics in class VII-8 SMP 3 Palangkaraya and describe the teacher's role in motivating students in learning. This type of approach used in this study is a qualitative approach, namely with information, correc fact and reliable. Subjects in this study were the teacher in class VII-8. The data used is primary data and secondary data collection techniques used in data observation, interviews, and documentation. Analysis using the technique proposed by Milles and Hubermen namely data reduction, data display, and verification of decision making. These results indicate that BK teacher acts as a motivator and as a mentor in terms of motivating learners to learn math at grade VII-8 SMP 3 Palangkaraya.